2014
DOI: 10.5090/kjtcs.2014.47.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Bronchioloalveolar Carcinoma in a Juvenile Rhadomyosarcoma Patient

Abstract: Primary tumors of the lung are uncommon in pediatric patients, particularly bronchioloalveolar carcinoma (BAC). An 11-year-old female suffering from back pain for 1 month was referred to Seoul St. Mary's Hospital for treatment of a pathologic fracture of the lumbar spine. Comprehensive evaluation disclosed numerous pulmonary metastases of rhabdomyosarcoma (stage IV). During chemotherapy, most of the lung lesions regressed, with the exception of two nodules. Wedge resections, intended for diagnosis and cure, yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…Interestingly, this SMN developed outside of the patient's radiation field and with a relatively short latency from diagnosis, suggesting that an underlying genetic cancer predisposition may be contributing. The occurrence of minimally invasive adenocarcinoma of the lung in a young patient with metastatic RMS has only been previously described once in the literature . In contrast to the case presented by Bradee et al., the adenocarcinoma in this patient was likely present at diagnosis of pulmonary metastatic RMS, as two nodules that failed to resolve with RMS‐directed therapy were found to both be minimally invasive adenocarcinoma.…”
contrasting
confidence: 65%
“…Interestingly, this SMN developed outside of the patient's radiation field and with a relatively short latency from diagnosis, suggesting that an underlying genetic cancer predisposition may be contributing. The occurrence of minimally invasive adenocarcinoma of the lung in a young patient with metastatic RMS has only been previously described once in the literature . In contrast to the case presented by Bradee et al., the adenocarcinoma in this patient was likely present at diagnosis of pulmonary metastatic RMS, as two nodules that failed to resolve with RMS‐directed therapy were found to both be minimally invasive adenocarcinoma.…”
contrasting
confidence: 65%
“…AIS has also been reported as a SMN following a variety of pediatric cancers . Choi et al recently published the only reported case of AIS as a SMN after RMS . They describe an 11‐year‐old female presenting with stage IV RMS of unspecified non‐pulmonary origin with concurrent lung nodules.…”
Section: Discussionmentioning
confidence: 99%